The Efficacy of Seaweed Powder Application for Enhancing Wastewater Quality in the Cepuk Textile Industry of Nusa Penida - Sundari, Cokorda Dewi; Arjani, Ida Ayu; Wilan Krisna, Luh Ade; Karta, I Wayan; Jirna, I Nyoman; Suriani, Ni Luh; Mariani, Mariani (Tropical Plantation Journal, 2024)
Introduction: The traditional textile art of Tenun Cepuk from Nusa Penida is highly valued for its intricate designs and cultural importance. Nevertheless, the environmental predicament posed by the textile industry's wastewater, particularly due to dye-related contamination, is substantial and necessitates sustainable remedies. Seaweed powder shows considerable promise as an adsorbent for addressing dye wastewater issues within the textile sector. An essential aspect of this endeavor is to explore the dynamic relationship between different thicknesses and contact durations, as it is pivotal in optimizing the adsorption capacity and effectiveness of seaweed powder for treating dye wastewater..Method: This research, utilizing an Experimental research design with a Posttest Only Control Group Design, is conducted to evaluate the influence of an intervention on the experimental group as compared to the control group. Euchema cottonii seaweed, sourced from Nusa Penida, is employed as the adsorbent. Different thicknesses of seaweed powder, namely 5 cm, 10 cm, and 15 cm, are added to tanks. Subsequently, wastewater samples from the Cepuk weaving process are introduced into each of the experimental tanks, alongside a control group. The process is allowed to continue for 24 and 72 hours as varying contact durations. The adsorption outcomes are then subjected to analysis, including parameters such as TSS, TDS, BOD5, and COD, at the Panureksa Denpasar Laboratory.Results: The application of seaweed powder as an adsorbent proves to be efficient in decreasing TDS, TSS, BOD5, and COD levels in Cepuk textile dye wastewater. The extent of reduction relies on the thickness of the adsorbent and the duration of contact. Increased thickness of the adsorbent results in a pronounced reduction in TDS, TSS, BOD5, and COD levels, leading to an improvement in the quality of wastewater and a safer environmental impact. Specifically, an adsorbent with a thickness of 15 cm effectively reduces TDS to permissible levels. Extended contact times also lead to a significant decrease in these levels..Conclusion: The application of seaweed powder is a viable method for reducing TDS, TSS, BOD5, and COD levels in textile dye wastewater. The thickness of the adsorbent and the duration of contact play a substantial role in improving the quality of the wastewater.